Effect of sevoflurane on hemodynamic response during cardiopulmonary bypass in cardiac surgery patients: A randomized controlled trial. - Lam, Vu Thanh; Ly, Nguyen Minh (Journal of Cardiovascular & Thoracic Research, 2025)
Introduction: Sevoflurane has little effect on hemodynamics and has been shown to have a hemodynamic stabilizing effect in the pre- and post-cardiopulmonary bypass (CPB) period in patients undergoing cardiac surgery. However, clinical data on the effect of sevoflurane on the hemodynamic response during CPB in patients undergoing cardiac surgery are lacking. This study investigated whether the hemodynamic stabilizing effect of sevoflurane is demonstrated during CPB time in cardiac surgery patients. Methods: Fifty-five patients undergoing cardiac surgery under CPB were randomly assigned to anesthesia with sevoflurane (intervention group) or propofol (control group) during CPB. The primary outcomes were changes in hemodynamic parameters and the need for inotropes and vasopressors during CPB. Secondary outcomes were morbidity and mortality within 30 days after surgery. Results: The mean arterial pressure (MAP) at 5 minutes after heartbeat recovery and the end of CPB as well as central venous oxygen saturation (ScvO2) at 5 minutes after heartbeat recovery and cardiac index (CI) at the end of CPB of group S-CPB (intervention group) were higher than those of group P-CPB (control group). In addition, the proportion of patients using dobutamine and noradrenaline during CPB was also lower in group S-CPB. Conclusion: In conclusion, in patients undergoing cardiac surgery under CPB, the use of sevoflurane for anesthesia during CPB results in hemodynamic stability with less need for inotropes and vasopressors during CPB but morbidity and mortality within 30 days after surgery were not significantly different when compared with the control group.